Modelling drug use: methods to quantify and understand hidden processes - Godfrey, Christine (EMCDDA scientific monograph series, 2001)
Dynamic modelling is a quantitative technique used by scientists when data are scarce to generate estimates, test hypotheses and forecast trends. This publication explores the potential role of dynamic modelling in helping to interpret data on drug use and its consequences in the European Union. The monograph contains over a dozen expert reviews on modelling techniques and their use in estimating drug use and related health consequences. The publication presents dynamic modelling as a valuable analytical tool, not only in improving insight into drug use, but also in contributing to the development of evidence-based drug policies and interventions.